LEVEL OF COMPETITIVENESS OF BUILDING PRODUCTS TO INCREASE INNOVATIVE SUCCESS (Academicia Globe: Inderscience Research, 2022)
The scientific article describes the scientific and theoretical foundations for improving the efficiency of assessing the competitiveness of products based on innovative measures at the enterprise of construction products. In order to increase the competitiveness of construction products, first of all, the factors influencing it are identified, the degree of influence of these factors is assessed, and suggestions and recommendations are made on how to increase the competitiveness of products due to the success of product innovations in the construction markets.